Development of the Human Digestive System Electronic Student Worksheet Using a Combination of Canva and Liveworksheet - Anantyarta, Primadya; Sa'diyah, Abidatus (Bioeducation Journal, 2025)
This research aims to develop E-LKPD (electronic Student Worksheet) teaching materials using the Live worksheet web platform on human digestive system material for class XI high school students. The background to this research is the need for innovative and interactive teaching materials that can support effective and efficient learning processes in the digital era. The research method used is Research and Development (R&D) with a 4D model (define, design, development, disseminate. The results of the analysis of the main needs for teaching materials show that 100% of the 7 students are interested in studying the biology of the human digestive system using mobile phones, as many as 100% of the 7 students need alternative teaching materials that can be used to study the digestive system and 100% of students agree to develop electronic-based teaching materials on the human digestive system.